Excretory system learning: What is the relationship between critical thinking skills and biology learning motivation? - Hanifia Rizky; Dalia Sukmawati; R Rusdi (Universitas Negeri Jakarta, 2020)
This research aims to find out the relationship between critical thinking skills and students’ learning motivation in the excretory system content. The research employs a descriptive method with correlation approach. The research population includes students of Madrasah Tsanawiyah Negeri of a school in Jakarta Timur, Indonesia. Sampling is conducted using multi-stage sampling. Samples used are 95 students of Grade IX. The research instruments consist of critical thinking skill test and learning motivation questionnaire. Data analysis uses regression analysis technique. The regression equation is compiled and tested with variance analysis using ANOVA table with F-test. The multiple regression hypothesis testing carries out by compiling multiple regression equation and testing using variance analysis with t-test. The research results indicate pxy, means that there is a correlation between critical thinking and learning motivation. The research recommendation is that the excretory system learning activity empowers critical thinking so that it improves motivation to learn the excretory system.